Gamifikasi Non Digital dalam pembentukan Karakter Islami pada Siswa di PKBM KBRI Kuala Lumpur Malaysia - Ahmad Muntachob Choirul Umam; Syamsul Arifin; Mohammad Darwis (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to describe the implementation of non-digital gamification in strengthening students’ Islamic religious character. The research employed a qualitative approach. Data were collected through classroom observations, interviews with teachers and students, and documentation of classroom activities. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings show that non-digital classroom activity-based gamification integrated with Islamic values can increase students’ learning engagement and strengthen Islamic religious character, particularly in honesty (sidiq), responsibility (amanah), discipline (nidhom), learning motivation, and social cooperation (ta’awun). Teachers play a key role as facilitators by linking game-based activities with the habituation of religious attitudes during the learning process. Therefore, non-digital gamification can serve as a relevant learning innovation for strengthening Islamic religious character in non-formal education settings.